2022
DOI: 10.1519/ssc.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Cutting: An Evidence-Based Coaching Framework to Reduce Anterior Cruciate Ligament Injury Risk

Abstract: Few evidence-based guides exist to support coaches in delivering technical elements of cutting that may reduce the risk of anterior cruciate ligament (ACL) rupture. In isolation, balance exercises, jump landing, cutting movements, as well as modifying the penultimate step, may alter biomechanics favorably during this maneuver. By breaking this serial skill into its constituent parts, the coach is afforded an opportunity to observe trainable deficits, and allows the player more opportunity for practice. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 139 publications
(287 reference statements)
0
4
0
Order By: Relevance
“…Cutting kinematics are closely related to both cutting performance and ACL loading [ 11 , 17 , 32 , 116 , 117 ]. The aims of the present study were twofold: First, to develop a cutting technique modification training program that targets specific kinematics associated with improved performance and reduced injury risk potential while considering various principles from the motor-learning domain, and, second, to investigate its effects on cutting performance and movement quality in adolescent American football players.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cutting kinematics are closely related to both cutting performance and ACL loading [ 11 , 17 , 32 , 116 , 117 ]. The aims of the present study were twofold: First, to develop a cutting technique modification training program that targets specific kinematics associated with improved performance and reduced injury risk potential while considering various principles from the motor-learning domain, and, second, to investigate its effects on cutting performance and movement quality in adolescent American football players.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that increased velocity at key instances of the penultimate foot contact and final foot contact is largely associated with cutting performance [ 79 , 116 ]. Thus, the underpinning idea is to develop a pronounced deceleration ability to brake effectively (i.e., apply an adequate horizontal braking force to reduce whole-body momentum to an optimal level for the subsequent cutting movement) [ 31 , 125 , 126 ] and rapidly over the shortest possible distance/time (i.e., with very few braking steps/short braking contact time) [ 127 ] prior to direction change to maintain a high approach speed for as long as possible [ 32 ]. Effective braking was also trained in the intervention; however, during testing, some athletes occasionally fell into shuffle-step movement patterns in the transition from approach to cutting, which are associated with lower velocity maintenance [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations